2018
DOI: 10.2147/ndt.s155478
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization within, and interactions between, the default mode and dorsal attention networks in relapsing-remitting multiple sclerosis

Abstract: Background and purposeThe effects of the interactions between the default mode network (DMN) and the dorsal attention network (DAN), which present anticorrelated behaviors, in relapsing-remitting multiple sclerosis (RRMS) are poorly understood. This study used resting-state functional connectivity (FC) and the Granger causality test (GCT) to examine changes in the undirected and effective functional network connectivity (FNC) between the two networks during the remitting phase in RRMS patients.Patients and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…All the remaining volumes were processed, including slice correction, head realignment, spatial normalization to MNI space with high-resolution T1WI registration, resampling to 3 mm isotropic voxels, and 6 mm smoothing. The standard preprocessing procedures have been described in our previous studies [11]. In addition, subjects with head movement in the cardinal directions (x, y, z) >2 mm and a maximum rotation (x, y, z) >2° were excluded.…”
Section: Image Acquisition and Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…All the remaining volumes were processed, including slice correction, head realignment, spatial normalization to MNI space with high-resolution T1WI registration, resampling to 3 mm isotropic voxels, and 6 mm smoothing. The standard preprocessing procedures have been described in our previous studies [11]. In addition, subjects with head movement in the cardinal directions (x, y, z) >2 mm and a maximum rotation (x, y, z) >2° were excluded.…”
Section: Image Acquisition and Preprocessingmentioning
confidence: 99%
“…Additionally, patients with MS with cognitively impairment display reduced eigenvector centrality dynamics in the DMN, frontoparietal network, and visual network [10]. Our previous study found that abnormalities of the attention network, which is more associated with externally directed cognition, have been observed in relapsing-remitting MS (RRMS); these abnormalities include decreased FC [11] and dynamic FC [12] within the network.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…All the preprocessing steps were carried out using the MATLAB 2012a platform (MathWorks, Inc., Natick, MA, USA). The standard preprocessing procedures have been described in our previous studies [11]. The main steps of preprocessing included the rst ten volumes of each session were discarded for the equilibrium state of the echo signal, slice correction, head realignment, spatial normalization to MNI space with high-resolution T1WI registration, resampling to 3 mm isotropic voxels, and 6 mm smoothing.…”
Section: Image Acquisition and Preprocessingmentioning
confidence: 99%
“…[ 12 ] In rs-fMRI, functional connectivity is widely used to reflect the neuronal intrinsic activity level in functional communication between regions. Previous studies had shown the MS patients’ impairment of the integrity in inter-network coupling and intra-network functional connectivity in the salience network, [ 13 ] default mode network, [ 14 , 15 ] sensorimotor network, [ 16 , 17 ] and visual network. [ 18 ] Another study [ 19 ] revealed that different immune pathogenic processes occur as the disease stage changes, which may lead to different cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%